Analysis Application of the Problem Based Learning (PBL) in Elementary Schools - Indah Wahyuningsih, Putri; Munfariqoh, Aqidatul; Tampubolon, Rina Anggita (Journal of Practice Learning and Educational Development, 2025)
This study aims to apply the Problem Based Learning (PBL) model in the learning process in Elementary Schools. Through a qualitative descriptive approach, this study describes how the Problem Based Learning (PBL) learning model is implemented by teachers. Data were obtained through observation, interviews, and documentation at SDN Jomblang 05 Semarang and analyzed by data triangulation. The results of the study indicate that teachers have implemented learning in accordance with the five stages of the Problem Based Learning (PBL) model syntax. Each stage runs effectively and has a positive impact on students' activeness, critical thinking skills, collaboration skills, and sense of responsibility in the learning process. In addition, the application of the Problem Based Learning model has an impact on the level of student understanding related to the material and students are more active in learning because they are involved in every learning process.